(untitled) - Pittau, Joseph (Cambridge, 1967)
The main purpose is to examine the political concepts of the articulate elite of early Meiji Japan and to see what kind of state the Meji leaders envisioned as they built the new nation and discussed the pros and cons of a representative constitutional government.
Keywords: Political science,Constitutional history,Khoa học chính trị,Lịch sử lập hiến; History,Lịch sử; Japan,Japan,Nhật Bản